Relationship Between Motivation and Performance in K.C.S.E Biology In Selected Secondary Schools In Nyakach District, Kisumu County, Kenya - Albert, Mr. Owino Ogutu; Osman, Prof. Ahmed; Alice M., Dr. Yungungu; O, Ogolla Bernard (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
This paper identifies and discusses motivation related factors and how they influenceperformance in K.C.S.E Biology in selected secondary schools in Nyakach Sub – county, KisumuCounty. The study was significant as performance in K.C.S.E Biology has been poor over theyears; hence need to find out causes. The study was guided by the systems theory advocated byGagne and Briggs (1979). The research was conducted through descriptive survey design byquantitative and qualitative approach. The target population was seven hundred and thirty Formfour students, eighteen Biology teachers, and fourteen Principals. Stratified random samplingwas used to select schools, purposive sampling for selecting teachers and Principals, form fourstudents were first stratified then selected through simple random sampling. Data was collectedusing questionnaires for students, teachers and interview schedule for principals. DescriptiveStatistics such as frequencies, percentages, correlation analysis, regression coefficient andcoefficient of determination were used to analyze data using Statistical Package for the SocialSciences Programme (SPSS). The finding was that there was positive relationship betweenmotivation and performance in K.C.S.E Biology. The study recommended that, teachers shouldalways introduce motivational variables in their teachings.